1974
DOI: 10.1037/h0037137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shape of receptor organ on the horizontal-vertical illusion in passive touch.

Abstract: In four experiments involving 156 5s, stimulus templates were traced onto the volar surface of 5's forearm. Experiment I showed that rotation of a T figure over 180° resulted in an illusion function, with a reversal of the effect at 90°. A similar function was obtained in Experiment II with an L figure, indicating the absence of a bisection effect. The component line along the shorter lateral axis was judged longer than that aligned with the longitudinal axis of the forearm. Experiments III and IV indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
(24 reference statements)
3
7
0
Order By: Relevance
“…Previous studies (Essock et al, 1992(Essock et al, , 1997Geldard & Sherrick, 1983;B. G. Green, 1982;Lechelt, 1988Lechelt, , 1992Vierordt, 1870;Weber, 1834Weber, /1996Wheat & Goodwin, 2000;Wong et al, 1974), as well as the results from Experiments 2 and 3, support this view. One could imagine, however, that other dimensions of tactile sensitivity, such as intensive or temporal dimensions, might also show anisotropy.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies (Essock et al, 1992(Essock et al, , 1997Geldard & Sherrick, 1983;B. G. Green, 1982;Lechelt, 1988Lechelt, , 1992Vierordt, 1870;Weber, 1834Weber, /1996Wheat & Goodwin, 2000;Wong et al, 1974), as well as the results from Experiments 2 and 3, support this view. One could imagine, however, that other dimensions of tactile sensitivity, such as intensive or temporal dimensions, might also show anisotropy.…”
Section: Methodssupporting
confidence: 72%
“…Several recent studies (Essock, Krebs, & Prather, 1992Fuchs & Brown, 1984;Geldard & Sherrick, 1983;B. G. Green, 1982;Lechelt, 1988Lechelt, , 1992Stevens & Patterson, 1995;Wheat & Goodwin, 2000;Wong, Ho, & Ho, 1974) have noted changes in sensitivity as a function of the orientation of the stimuli on the body; however, the only previous systematic studies (Vierordt, 1870;Weber, 1834Weber, /1996 of anisotropy, which included multiple test sites, have used the two-point threshold, a problematic measure of spatial sensitivity.…”
mentioning
confidence: 99%
“…For instance, Cholewiak (1999) showed no effect of direction when making judgments about two unseen tactile stimuli applied to the thigh (as we show here), whereas Green (1982) showed that participants significantly underestimated distances applied to the thigh in the longitudinal direction compared to the transverse direction. Similar findings have been replicated for estimates made about the hand (Longo & Haggard, 2011) and arms (Le Cornu-Knight et al, 2014;Green, 1982;Wong, Ho, & Ho, 1974) as well. With respect to the shin, investigations on tactile distance perception for the lower leg are lacking in the literature.…”
Section: Discussionsupporting
confidence: 54%
“…There have been a number of reports on discrepancies between tactile space and physical space 1 3 , 6 11 , 14 , 15 . For example, touch distances along the arm were perceived to be longer than those across the arm 3 , 7 , and touch locations on the arm were perceived to be closer to the wrist and the elbow 2 , 10 . Some studies investigated localization for touch and even pain on the dorsal surface of the hand and arm, and found that stimulus localization was more accurate (smaller uncertainty intervals) in the short axis than in the long axis 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%